2020
DOI: 10.1186/s12870-020-2287-8
|View full text |Cite
|
Sign up to set email alerts
|

Combined application of Ascophyllum nodosum extract and chitosan synergistically activates host-defense of peas against powdery mildew

Abstract: Background: Powdery mildew (PM) is an important disease of pea that reduce yield. Ascophyllum nodosum extract (ANE) and chitosan (CHT) are biostimulants used to improve plant health. Efficacy of ANE and CHT was assessed individually and in combination against pea powdery mildew. Results: Combined applications of ANE and CHT had a significant inhibitory effect on pathogen development and it reduced disease severity to 35%, as compared to control (90.5%). The combination of ANE and CHT enhanced the activity of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…The levels of mycotoxins, deoxynivalenol and sambucinol, were found to be lower in those wheat grains harvested from the plants treated with a combination of liquid seaweed extract and chitosan [150]. Similarly, the combination of liquid seaweed extract prepared from A. nodosum and chitosan inhibited the growth of Erisyphe pisi causing powdery mildew in pea [172]. Seasol Commercial ® (Seasol International, Bayswater, Australia), is an alkaline hydrolysis product prepared from Duvillaea potatorum and A. nodosum and was found to reduce the progression of Plasmodiophora brassicae, causing club-root in broccoli [144].…”
Section: Ascophyllum Nodosummentioning
confidence: 97%
“…The levels of mycotoxins, deoxynivalenol and sambucinol, were found to be lower in those wheat grains harvested from the plants treated with a combination of liquid seaweed extract and chitosan [150]. Similarly, the combination of liquid seaweed extract prepared from A. nodosum and chitosan inhibited the growth of Erisyphe pisi causing powdery mildew in pea [172]. Seasol Commercial ® (Seasol International, Bayswater, Australia), is an alkaline hydrolysis product prepared from Duvillaea potatorum and A. nodosum and was found to reduce the progression of Plasmodiophora brassicae, causing club-root in broccoli [144].…”
Section: Ascophyllum Nodosummentioning
confidence: 97%
“…It is clear from these results the effective role of algae extracts in combating fungal diseases affecting plants, and this has been proven by several previous studies. Patel et al (2020) stated that the combination of the extract of Ascophyllum nodosum and chitosan owned a respectable inhibitory effect on powdery mildew of peas since it reduced disease severity to 35%, as compared to control (90.5%). Esserti et al (2016) found that extracts of the brown algae Cystoseira myriophylloides, Laminaria digitata, and Fucus spiralis significantly reduced disease severity of Verticillium dahliae and Agrobacterium tumefaciens in tomato plants.…”
Section: Effect Of Algal Extract and Algal Products On Disease Severi...mentioning
confidence: 99%
“…There are numerous examples of chitosan application on vegetable crops; however, the obtained results are not always consistent since the various studies differ in their methodological approach (time and dose of application), while chitosanbased biostimulant products may also differ in chemical composition and chitosan content, which further increases heterogeneity in biological effects [77,78,[81][82][83]. The primary use of chitosan in agriculture is based on its eliciting effects on the biosynthesis of protective biomolecules against pests and pathogens [14,84,85], as well as on the up-regulation of defensive genes [86,87].…”
Section: Practical Applications Of Chitosan On Vegetable Cropsmentioning
confidence: 99%